Do callers of young children with fever follow the self-care recommendations given by a nursing triage line? - Sofiya Manji; Charlene Garner; Delores Steinlicht; Sarah Edwards; Sheila McDonald (International Journal of Population Data Science, 2018)
Introduction The management of fever can be a stressful situation for caregivers of young children. Accessing emergency departments and urgent care centres (ED/UCCs) due to concerns about fever and the potential consequences of child fever is common, despite fever rarely being considered a medical emergency.